The Reconstruction of the Concept of Waqf Muaqqat in the Hanafi Perspective: Relevance and Implementation in the Modern Era - Ermawati, Elda; Hamidah, Hamidah; Noor Sayuti, Muhammad; Rofi’i, Rofi’i (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2025)
waqf is actually one of the Islamic financial instruments that has a strategic role in improving the social and economic welfare of the community. Traditionally, waqf is known as a form of permanent donation, but the concept of muaqqat waqf (temporary waqf) has also become part of the discussion of Islamic jurisprudence. The purpose of this study is to examine in more depth the reconstruction of the concept of waqf muaqqat from the perspective of the Hanafi school of thought and its implementation and relevance in the modern era. The method used by the researcher is a qualitative method based on literature studies with data sources obtained from fiqh books, academic literature, and waqf regulations, journal books and other credible sources. The results of this study indicate that the Hanafi school of thought allows temporary waqf where this is a solution for sustainable waqf asset management. Furthermore, the researcher also provides research recommendations in the form of the need for regulations that are able to accommodate and support Islamic financial institutions in an effort to achieve optimal implementation of waqf muaqqat in the context of Islamic economics.